Bone integration capability of a series of strontium‐containing hydroxyapatite coatings formed by micro‐arc oxidation. Issue 9 (24th January 2013) - Yan, Jun; Sun, Ji‐Feng; Chu, Paul K.; Han, Yong; Zhang, Yu‐Mei
Abstract : Strontium‐containing hydroxyapatites (Sr‐HA) combine the desirable bone regenerative properties of hydroxyapatites (HA) with anabolic and anti‐catabolic effects of strontium cations. In the present work, a series of Sr y HA [Sr y Ca(10− y ) (PO4 )6 (OH)2 ; y = 0, 0.5, 1, 2] coatings on titanium are produced by micro‐arc oxidation (MAO), and the effects of the in vivo osseointegration ability of the coatings are investigated by using a rabbit model. All samples are subjected to biomechanical, surface elemental, micro‐CT and histological analysis after 4 and 12 weeks of healing. The obtained results show that the MAO‐formed coatings exhibit a microporous network structure composed of Sr y HA/Sr y HA–Sr x Ca(1‐ x ) TiO3 /Sr x Ca(1‐ x ) TiO3 –TiO2 multilayers, in which the outer Sr y HA and intermediate Sr y HA–Sr x Ca(1‐ x ) TiO3 layers have a nanocrystalline structure. All Sr‐HA coated implants induce marked improvements in the behavior of bone formation, quantity and quality of bone tissue around the implants than the control HA implant and in particular, the 20%Sr‐HA coating promotes early bone formation as identified by polyfluorochrome sequential labeling. The bone‐to‐implant contact is increased by 46% ( p < 0.05) and the pull‐out strength is increased by 103% over the HA group ( p < 0.01). Extensive areas of mineralized tissue densely deposit on the 20%Sr‐HA coating after biomechanical testing, and the greatest improvement of bone microarchitecture are observed around the 20%Sr‐HA implant. The identified biological parameters successfully demonstrate the osteoconductivity of 20%Sr‐HA surfaces, which results not only in an acceleration but also an improvement of bone–implant integration. The study demonstrates the immense potential of 20%Sr‐HA coatings in dental and orthopedic applications. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2465–2480, 2013.